Review of the Federal Ocean Acidification Research and Monitoring Plan (National Academies Press, 2013)
"The world's ocean has already experienced a 30% rise in acidity since the industrial revolution, with acidity expected to rise 100 to 150% over preindustrial levels by the end of this century. Potential consequences to marine life and also to economic activities that depend on a healthy marine ecosystem are difficult to assess and predict, but potentially devastating. To address this knowledge gap, Congress passed the Federal Ocean Acidification Research and Monitoring (FOARAM) Act in 2009, which, among other things, required that an interagency working group create a "Strategic Plan for Federal Research and Monitoring of Ocean Acidification." Review of the Federal Ocean Acidification Research and Monitoring Plan reviews the strategic plan on the basis of how well it fulfills program elements laid out in the FOARAM Act and follows the advice provided to the working group in the NRC's 2010 report, Ocean Acidification: A National Strategy to Meet the Challenges of a Changing Ocean. This report concludes that, overall, the plan is strong and provides a comprehensive framework for improving our understanding of ocean acidification. Potential improvements include a better defined strategy for implementing program goals, stronger integration of the seven broad scientific themes laid out in the FOARAM Act, and better mechanisms for coordination among federal agencies and with other U.S. and international efforts to address ocean acidification."--